2006
DOI: 10.1093/bioinformatics/btl417
|View full text |Cite
|
Sign up to set email alerts
|

Local similarity analysis reveals unique associations among marine bacterioplankton species and environmental factors

Abstract: The algorithms are implemented in Splus/R and they are available upon request from the corresponding author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
255
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(259 citation statements)
references
References 21 publications
2
255
1
1
Order By: Relevance
“…This notion is supported by the observation that phylogenetically related microbes have a tendency to positively co-occur (Lozupone et al, 2012). Recent studies suggest that the microbial relationships shown in correlation interaction networks can be used to determine drivers in environmental ecology (Ruan et al, 2006;Steele et al, 2011;Zhou et al, 2011;Lima-Mendez et al, 2015) or contribution to habitat niches or disease (Chaffron et al, 2010;Arumugam et al, 2011;Greenblum et al, 2012;Oakley et al, 2013;Goodrich et al, 2014;Buffie et al, 2015). Correlation is also a powerful tool to help researchers with hypothesis generation, such as determining which interactions might be biologically relevant in their system, and should be given further study (for example, through co-culturing or whole-genome sequencing).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This notion is supported by the observation that phylogenetically related microbes have a tendency to positively co-occur (Lozupone et al, 2012). Recent studies suggest that the microbial relationships shown in correlation interaction networks can be used to determine drivers in environmental ecology (Ruan et al, 2006;Steele et al, 2011;Zhou et al, 2011;Lima-Mendez et al, 2015) or contribution to habitat niches or disease (Chaffron et al, 2010;Arumugam et al, 2011;Greenblum et al, 2012;Oakley et al, 2013;Goodrich et al, 2014;Buffie et al, 2015). Correlation is also a powerful tool to help researchers with hypothesis generation, such as determining which interactions might be biologically relevant in their system, and should be given further study (for example, through co-culturing or whole-genome sequencing).…”
Section: Introductionmentioning
confidence: 91%
“…For example, CoNet acknowledges that various techniques have different strengths and weaknesses and/or are designed to optimally detect different functional relationships, and thus uses an ensemble method with the ReBoot procedure for P-value computation to combine information from several different standard comparison metrics. Local Similarity Analysis (LSA) (Ruan et al, 2006;Beman et al, 2011;Steele et al, 2011;Xia et al, 2013) is optimized to detect non-linear, time-sensitive relationships and can be used to build correlation networks from time-series data. The Maximal Information Coefficient (MIC) (Reshef et al, 2011) is a non-parametric method designed to capture a wide range of associations without limitation to specific function types (such as linear or exponential) and to give similar scores to equally noisy relationships of different types.…”
Section: Introductionmentioning
confidence: 99%
“…For the network analysis, we first used extended Local Similarity Analysis to find the timedependent correlations between species-level OTUs and environmental variables (Ruan et al, 2006;Xia et al, 2011). The Local Similarity Analysis calculates synchronous and time-delayed correlations based on the normalized ranked data and produces correlation coefficients that are analogous to a Spearman's ranked correlation (Ruan et al, 2006).…”
Section: Statistical and Network Analysismentioning
confidence: 99%
“…The Local Similarity Analysis calculates synchronous and time-delayed correlations based on the normalized ranked data and produces correlation coefficients that are analogous to a Spearman's ranked correlation (Ruan et al, 2006). Then, we used Cytopscape v2.8.3 (Shannon et al, 2003) for network visualization and topological analysis, as described in Supplementary Information S3.…”
Section: Statistical and Network Analysismentioning
confidence: 99%
“…Networks were generated using the extended local similarity analysis (eLSA) program (Ruan et al, 2006;Xia et al, 2013) which implements the local similarity analysis with latest improvements for high-throughput data. We used eLSA to identify global, time-lagged, Spearman correlations between bacterial and environmental nodes at all depths.…”
Section: Network Analysismentioning
confidence: 99%